Renal Oncocytoma and Retroperitoneal Ancient Schwannoma: A Benign Mimic of Metastatic Renal Cell Carcinoma - Tyler J. Maiers; Daniel C. Wang; Ali H. Houjaij; Oussama M. Darwish (Case Reports in Urology)
Renal oncocytomas and retroperitoneal schwannomas are rare and typically benign tumors with characteristic histopathologic features. Ideal management of both renal oncocytoma and retroperitoneal schwannoma is surgical resection. We present a rare case of a 63-year-old man with multifocal renal oncocytoma and retroperitoneal ancient schwannoma which, preoperatively, masqueraded as metastatic renal cell carcinoma. Both tumors were successfully resected surgically. Immunochemistry and histopathology confirmed each diagnosis.